(untitled) (مجلة إحالات, 2026)
This study investigates teachers’ and learners’ attitudes towards the efficiency of using essay-scoring rubrics in increasing learners’ self-efficacy. To prove or reject the hypothesis which assumes that using essay-scoring rubrics while assessing learners’ compositions would affect their self-efficacy, a quantitative descriptive method was followed where two questionnaires were distributed to twenty-one teachers and fifty-eight second-year students at the department of English in 8 Mai 1945- Guelma- University. The analysis of the questionnaires revealed that the majority of the respondents believe that rubrics have a positive impact on the learners’ self-efficacy. Accordingly, some practical recommendations were suggested to teachers to help them in increasing students’ self-efficacy.